Marketing: Based on first principles - Palmatier, Robert W.; Crecelius, Andrew T. (London Bloomsbury academic, 2025)
a structured, fundamental approach to strategy that identifies and addresses four core, unchanging realities: all customers differ, all customers change, all competitors react, and all resources are limited. By systematically analyzing these foundational principles, marketers can develop effective, adaptable strategies, manage customer heterogeneity, anticipate competitive responses, and make optimal resource decisions to achieve marketing objectives in a dynamic environment.